Evolution of Childhood Narcolepsy and Cataplexy - J Gordon Millichap (Pediatric Neurology Briefs, 2014)
Investigators at University of Bologna and other centers in Italy, Finland, USA, and UK, performed clinical, polysomnographic, and cataplexy-video assessments at diagnosis (mean age of 10 +/- 3 years) and after a median follow-up of 3 years.